Urban Sprawl Typology in Semarang City - Aprillia, Yutri; Pigawati, Bitta (Forum Geografi, 2018)
The population and economic growth increase the need of space leading to an increase in built-up area. There is an increased activity in the city centre which results in the residents feeling less comfortable to live in the area. Hence, the growth of the settlement area tends to head towards the periphery. This condition is an indication of the developments of the built-up area in the periphery. Urban sprawl is a phenomenon of development of an irregular built-up area which leads to the suburbs. Urban development as a result of urban sprawl will trigger an increase in the demand for supporting facilities and infrastructure. An urban Sprawl in Semarang City has resulted in the establishment of residential areas in a conserved region, which is against zoning regulations in the Semarang City Spatial Planning Document (RTRW). Urban Sprawl Typology Research in Semarang City aims to analyse the urban sprawl typology in the city. By knowing the typology, it can minimise the impact of urban sprawl. This research was conducted using the remote sensing method and geographic information system (GIS) with the Shannon's Entropy approach. The results indicated that in 2006 and 2016, urban sprawl in Semarang City had three types of typology that can be classified as typology I (low level), typology II (medium level) and typology III (high level). The impact of urban sprawl on typology II and III can be minimised through the provision of affordable housing with adequate infrastructure, and an improvement in the permit system for housing and settlement development.